Tarnished are the stars - Thor, Rosiee (Scholastic Press, 2019)
A secret beats inside Anna Thatcher's chest: An illegal clockwork heart. Anna works cog by cog -- donning the moniker Technician -- to supply black market medical technology to the sick and injured, against the Commissioner's tyrannical laws. Nathaniel Fremont, the Commissioner's son, has never had to fear the law. Determined to earn his father's respect, Nathaniel sets out to capture the Technician. But the more he learns about the outlaw, the more he questions whether his father's elusive affection is worth chasing at all. Their game of cat and mouse takes an abrupt turn when Eliza, a skilled assassin and spy, arrives. Her mission is to learn the Commissioner's secrets at any cost -- even if it means betraying her own heart. When these uneasy allies discover the most dangerous secret of all, they must work together despite their differences and put an end to a deadly epidemic -- Before the Commissioner ends them first.